Hepatocytes derived from human induced pluripotent stem cells: Towards establishing an in vitro model for assessing population variability in hepatotoxicity testing - Xiugong Gao; Rong Li; Kayla Campasino; Miranda R. Yourick; Yang Zhao; Robert L. Sprando; Jeffrey J. Yourick (Current Research in Toxicology)
Interindividual differences in response to chemicals have been typically addressed through the use of a 10-fold default “uncertainty” factor. It was only recently that in vitro models emerged to quantitatively assess interindividual variability in the human population for specific chemicals. In the current study, we attempted to establish an in vitro model for assessing population variability in hepatotoxicity testing using a panel of hepatocytes derived from nine human induced pluripotent stem cell (iPSC) lines belonging to three different ethnic groups, Black or African American, Latino or Hispanic, and Non-Hispanic White. We demonstrated that the panel of iPSC-derived hepatocytes manifested diversity in hepatic function assays, in global and hepatic gene expressions, and in cytotoxic responses to four well know hepatotoxicants with distinct mechanisms of toxicity: acetaminophen, troglitazone, diglycolic acid, and usnic acid. However, due to the unavailability of model compounds with ethnicity specific toxicity as well as the small number of individuals in each ethnic group (n = 3), ethnic-specific effects were not observed using the model.